Cardiovascular effects of (R)- and (S)-verapamil and racemic verapamil in humans: a placebo-controlled study - Busse, Dagmar; Templin, Silke; Mikus, Gerd; Schwab, Matthias; Hofmann, Ute; Eichelbaum, Michel; Kivistö, Kari T. (European journal of clinical pharmacology, 2006)
To characterise the comparative potency of optically pure (R)- and (S)-verapamil as regards negative dromotropic effects on atrioventricular (AV) node conduction and to compare the hemodynamic effects of single doses of the enantiomers in healthy volunteers.
Gesehen am 07.10.2021